Distance between Great Vessels and the Lumbar Spine: MRI Study for Anterior Longitudinal Ligament Release Through a Lateral Approach - Marchi, Luis; Pimenta, Luiz; Oliveira, Leonardo; Fortti, Fernanda; Amaral, Rodrigo; Abdala, Nitamar (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Objective Anterior column reconstruction using the lateral transpsoas approach requires sectioning of the anterior longitudinal ligament while protecting the great vessels. Our aim was to study the anatomical plane of separation between the retroperitoneal vessels and the anterior aspect of the lumbar spine as they relate to safety in the lateral transpsoas anterior column reconstruction procedure.Method A total of 100 T2-weighted magnetic resonance imaging (MRI) examinations were studied. Measurements were obtained for each vertebral body and for each intervertebral disk levels from L1–L2 to L4–L5, and for these vessels: abdominal aorta, inferior vena cava , and common iliac vessels. The following parameters were obtained: (sagittal) total lumbar lordosis and segmental lordosis; (axial) closest distance (areolar space [AS]) between the lumbar spine and vessels; and position of the great vessels.Results The AS was differently distributed for the abdominal aorta and the inferior vena cava. Average values for the inferior vena cava were larger at upper levels (p < 0.001; range: 0.2–9.2 mm), and there were differences between the arteries among the levels (p < 0.001; range: 1.0–4.3 mm) but with no clear difference between the upper and lower lumbar spine. A narrower AS was found at the intervertebral disk level compared with the adjacent vertebral body. At L4–L5, the veins usually lay over the anterior border of the lumbar spine, with substantially wider AS at other lumbar levels.Conclusion The plane between the great vessels and the lumbar spine is differently distributed along the lumbar spine and is especially narrow at lower lumbar levels and in front of the intervertebral disk. The results shown here may help guide surgical decision making for the lateral anterior column reconstruction and may aggregate data from dislocation of the vessels in the lateral decubitus and individualized analysis.
Keywords: XLIF; great vessels; lateral interbody fusion; magnetic resonance imaging; adult spine deformity